Tinjauan Yuridis Putusan Pra Peradilan Terhadap Badan Narkotika Nasional (BNN) Provinsi Kalimantan Timur Oleh Pelaku Penyalahgunaan Narkotika - Sundari Prasetyani; Zainab Ompu Jainah (Universitas Sang Bumi Ruwa Jurai, 2023)
Narcotics are substances that primarily have anesthetic effects, or can reduce consciousness, and can also cause other physical and mental symptoms if used continuously and wildly with the result, among other things, of becoming dependent on these substances. Narcotics abuse is the use without rights and against the law which is carried out not for the purpose of treatment, therapy because you want to enjoy its effects, in excessive amounts, irregularly, and lasts long enough to cause physical, mental and social health problems, this is in line with increasing activity. distribution of illegal narcotics by a network of international groups to developing countries. Types of class I drugs are heroin/putaw, cocaine, marijuana, methamphetamine, etc., a narcotics crime is an act that violates the provisions of the narcotics law, in this case Law Number 35 of 2009 concerning narcotics and other provisions including and/or does not conflict with the Law. The problem in this research is how the pretrial decision of the BNN East Kalimantan Province (Tenggarong) regarding narcotics abuse is based on decision number 1/Pid.Pra/2023/PN.Trg, the legal basis in the pretrial decision of the BNN East Kalimantan Province based on decision number 1/Pid .Pra/2023/PN.Trg. The research method uses a normative juridical approach, the types of data used are primary data and secondary data. Data collection through decision research and field research and analyzed qualitatively, data processing through editing, data classification, and data systemization.